DNA sequence recognition by an isopropyl substituted thiazole polyamide. - James, P; Merkina, E; Khalaf, A; Suckling, C; Waigh, R; Brown, T; Fox, K (2004)
We have used DNA footprinting and fluorescence melting experiments to study the sequence-specific binding of a novel minor groove binding ligand (thiazotropsin A), containing an isopropyl substituted thiazole polyamide, to DNA. In one fragment, which contains every tetranucleotide sequence, sub-micromolar concentrations of the ligand generate a single footprint at the sequence ACTAGT. This sequence preference is confirmed in melting experiments with fluorescently labelled oligonucleotides. Experiments with DNA fragments that contain variants of this sequence suggest that the ligand also binds, with slightly lower affinity, to sequences of the type XCYRGZ, where X is any base except C, and Z is any base except G.